Remote-mode microsphere nano-imaging: new boundaries for optical microscopes - Chen Lianwei (Institue of Optics and Electronics, Chinese Academy of Sciences, 2018)
Optical microscope is one of the most popular characterization techniques for general purposes in many fields. It is distinguished from the vacuum or tip-based imaging techniques for its flexibility, low cost, and fast speed. However, its resolution limits the functionality of current optical imaging performance. While microspheres have been demonstrated for improving the observation power of optical microscope, they are directly deposited on the sample surface and thus the applications are greatly limited. We develop a remote-mode microsphere nano-imaging platform which can scan freely and in real-time across the sample surfaces. It greatly increases the observation power and successfully characterizes various practical samples with the smallest feature size down to 23 nm. This method offers many unique advantages, such as enabling the detection to be non-invasive, dynamic, real-time, and label-free, as well as leading to more functionalities in ambient air and liquid environments, which extends the nano-scale observation power to a broad scope in our life.